Smaug variants in neural and non-neuronal cells - Fernández Alvarez, Ana Julia (2016)
Mammalian Smaug1/Samd4a is an mRNA regulator involved in synapse plasticity and additional non-neuronal functions. Here we analyzed the expression of Smaug1/Samd4a variants and Smaug2/Samd4b in primary hippocampal neurons and non-neuronal cell lines. We found that multiple Smaug proteins are present in several mammalian cell lines, including a canonical full length Smaug1, a Smaug1 variant that lacks the third exon, termed DEIII, and Smaug2, the product of a highly homologous gene. These three major isoforms are expressed differentially along neuron development and form cytosolic bodies when transfected in cell lines. By using luciferase reporters, we found that the DEIII isoform, which lacks 10 amino acids in the sterile α motif involved in RNA binding, shows a RNA-binding capacity and repressor activity comparable to that of the full length Smaug1. These observations are an important groundwork for molecular studies of the Smaug posttranscriptional pathway, which is relevant to neuron development, mitochondrial function and muscle physiology in health and disease.